ДИСКУРСИВНЫЕ ФУНКЦИИ ПАРАЛЛЕЛЬНО–ЛОГИЧЕСКИХ И ЦЕПНЫХ СВЯЗЕЙ - Мамедова C. (Eurasian Journal of Philology Science and Education, 2015)
The paper investigates the role of the parallel-logical and linear connections in the organization of the English and Azerbaijani discourses. These connections manifested by the various grammatical and lexical devices have important pragmatic and cognitive perspectives in the discourses of different types and genres. The typological differences in English and Azerbaijani have also an impact on these functions.